2020
DOI: 10.1016/j.yclnex.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Zinc status (intake and level) of healthy elderly individuals in Riyadh and its relationship to physical health and cognitive impairment

Abstract: s u m m a r yObjective: The aim of the current study was to assess the zinc status (intake and level) and its relationship to cognitive impairment among men and women aged 65 years and above in Riyadh, Saudi Arabia. Methods: A cross-sectional single-center study was conducted in 400 participants (200 men and 200 women) aged 65 years and above. They were randomly chosen in the primary care centers in Riyadh. The impaired cognitive functions were measured using the Abbreviated Mental Test Score (AMTS). Plasma zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In the present study, we revealed associations among dietary zinc intake, serum zinc level, and multiple comorbidities in people aged ≥ 60 years. In the geriatric population, the mean of serum zinc level was 80.5 (12.8) µg/dL, which corresponds to the findings of Barman et al [ 40 ] but is higher than that found by Alqabbani et al (70 (2.3) µg/dL) [ 41 ]. Approximately two-thirds of the population have been shown to be at risk of zinc deficiency (serum zinc concentration < 84 µg/dL) [ 39 ], which is one of the most common nutritional defects in older adults.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we revealed associations among dietary zinc intake, serum zinc level, and multiple comorbidities in people aged ≥ 60 years. In the geriatric population, the mean of serum zinc level was 80.5 (12.8) µg/dL, which corresponds to the findings of Barman et al [ 40 ] but is higher than that found by Alqabbani et al (70 (2.3) µg/dL) [ 41 ]. Approximately two-thirds of the population have been shown to be at risk of zinc deficiency (serum zinc concentration < 84 µg/dL) [ 39 ], which is one of the most common nutritional defects in older adults.…”
Section: Discussionsupporting
confidence: 86%
“…Approximately less than half of the males 42.86 %their levels of zinc are normal compared to around the third of females 35%. This result was in disagreement with Alqabbani & AlBadr (2020) as they found that Zinc deficiency was more in women than men. Grădinaru et al (2021) mentioned that zinc deficiencies have been reported in numerous pathologies, such as diabetes mellitus, but also in the physiological process of ageing.…”
Section: Minerals In the Bloodmentioning
confidence: 69%
“…Zinc deficiency may be associated with cognitive abilities, mood, and stress in aging. This mineral acts as a neurotransmitter and plays an important role in synaptic function and brain activity [57]. Iron deficiency anemia in older adults causes adverse effects such as a decline in strength and physical activity, cognitive impairment, frailty, and susceptibility to a greater number of comorbidities and mortality; constant monitoring and attention to diet provides better benefits than intensive treatments with supplements [58].…”
Section: Nutritional Indicators Of Elderlymentioning
confidence: 99%